PERAN POLICE GOES TO SCHOOL DALAM PELANGGARAN LALU LINTAS PADA PELAJAR SMA - paramadhanys, brimastya (Advances in Police Science Research Journal, 2020)
This research is motivated with an increase of number of traffic violation, that an intensive anticipation need to be done to minimize the number of traffic violation. This matter can be resolved by educating the community about traffic laws according to traffic regulations. Concept and theory approach in this research uses role theory, communication theory and management theory. Research methode uses qualitative method with comprehensive observation type. Data collection technique through interview, observation and documents study. Data analyst technique uses theory of Interactive Analysis Model Miles & Huberman, which are data reduction, data presentation and drawing conclusions or verification. According to the research was obtained some results that Police Goes To School program planning has been taken some anticipative and preventive steps in the form of duty tasks, safety of the fellows as priority and coordinate with related agencies. The implementation, instilling regulations and values of traffic in early age until further becoming guidelines for driving on the road. The school authority is part of supporting factor of Police Goes To School program. Facilities and infrastructures are very helpful for implementing this program. Fellow ability to support fellow performance in Police Goes To School program. Meanwhile, inhibit factors are the limited numbers of personnel and limited support of facilities and infrastructures are not yet optimal. Reffering to the research above a conclusion can be withdrawn that planning and socialization as well duty tasks has been done properly. Instilling regulations and values of traffic in early age have also been done as planned. Meanwhile the inhibit factors are limited personnel and facilities and infrastructures.